The Effect of Brand Image, Product Quality, E-WOM, and FOMO on Skintific Purchase Decisions - Esther Praja Anggriany Panggabean; Davin Vandello; Andika; Elisabeth Winata (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the influence of brand image, product quality, electronic word of mouth (e-WOM), and fear of missing out (FOMO) on purchasing decisions for Skintific products on Shopee in Medan City. The research aims to analyze the direct effects of these variables using a causal quantitative approach. Data were collected from 170 respondents and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that product quality, e-WOM, and FOMO significantly affect purchasing decisions, while brand image does not. These findings suggest that firms should strengthen product performance, online reviews, and digital marketing to improve consumer purchasing decisions. Keywords: Brand image; Product quality; Electronic word of mouth; Fear of missing out; Purchase decision; Skintific